Does Employee Wellbeing Mediate the Relationship between Job Characteristics and Job Performance in the Banking Industry? An Emerging Country Perspective - Hung, Ta Huy; Luu, Thi-Minh-Ngoc; Nguyen, Phuong Mai (International Review of Management and Marketing, 2024)
Banks play a crucial role in fostering and sustaining economic development within each country. Moreover, the rapid evolution of technology significantly influences the banking industry, ushering in profound changes in work dynamics. The post-COVID-19 era has accentuated the importance of employee well-being as a critical necessity for all workers. This study aims to elucidate the interplay between job characteristics, employee well- being, and job performance. A self-administered survey was conducted with employees working in the Vietnamese banking industry. After 4 months, we received 831 valid responses from 15 Vietnamese joint-stock commercial banks. SMARTPLS software was employed for structural equation modelling analysis. The findings shed light on the intricate relationships between job characteristics, employee well-being, and job performance. Building upon these insights, the study provides recommendations for Vietnamese banks to enhance job performance by refining job characteristics and fostering employee well-being.